The secret friend - Dunbar, Joyce; Craig, Helen (Cambridge, Mass. : Candlewick Press, 1999)
Panda feels a little hurt after helping his best friend Gander write a letter to Gander's secret friend.
Mode of access: Internet.
Keywords: Pandas -- Fiction; Geese -- Fiction; Letter writing -- Fiction; Best friends -- Fiction